Did Latvia's public works program mitigate the impact of the 2008 - 2010 crisis? - Mehtabul Azam; Céline Ferré; Mohamed Ihsan Ajwad (Institute for the Study of Labor (IZA), 2012)
To mitigate the impact of the 2008-2010 global financial crisis on vulnerable households, the Government of Latvia established Workplaces with Stipends, an emergency public works program that targeted registered unemployed people who were not receiving unemployment benefits. This paper evaluates the targeting performance and welfare impacts of the program. We exploit the over-subscription of Workplaces with Stipends to define a control group. The paper finds that the program was successful at targeting poor and vulnerable people, and that leakage to non-poor households was small. Using propensity score matching, the paper finds that the program's stipend mitigated the impact of job loss and, in the short term, raised participating household incomes by 37 percent relative to similar households not benefiting from the program. The paper also finds that the foregone income for this program was less than foregone incomes estimated in other countries. This suggests a dearth of income-generating opportunities in Latvia; thus the program provided temporary employment opportunities and helped the unemployed mitigate the impact of the crisis. However, relative to the depth of the crisis in Latvia, the Workplaces with Stipends program scale was small, which meant long waiting periods for program applicants.
Keywords: I38; J64; J68; 330; crisis; Latvia; public works; safety net; Arbeitsbeschaffung; Armutspolitik; Wirkungsanalyse; Finanzmarktkrise; Wirtschaftskrise; Lettland